Atlas of RNA editing events affecting protein expression in aged and Alzheimer’s disease human brain tissue - Ma, Yiyi; Dammer, Eric B.; Felsky, Daniel; Duong, Duc M.; Klein, Hans-Ulrich; White, Charles C.; Zhou, Maotian; Logsdon, Benjamin A.; McCabe, Cristin; Xu, Jishu; Wang, Minghui; Wingo, Thomas S.; et al. (Nature communications, 2021)
RNA editing is a feature of RNA maturation resulting in the formation of transcripts whose sequence differs from the genome template. Brain RNA editing may be altered in Alzheimer’s disease (AD). Here, we analyzed data from 1,865 brain samples covering 9 brain regions from 1,074 unrelated subjects on a transcriptome-wide scale to identify inter-regional differences in RNA editing. We expand the list of known brain editing events by identifying 58,761 previously unreported events. We note that only a small proportion of these editing events are found at the protein level in our proteome-wide validation effort. We also identified the occurrence of editing events associated with AD dementia, neuropathological measures and longitudinal cognitive decline in: SYT11 , MCUR1 , SOD2 , ORAI2 , HSDL2 , PFKP , and GPRC5B . Thus, we present an extended reference set of brain RNA editing events, identify a subset that are found to be expressed at the protein level, and extend the narrative of transcriptomic perturbation in AD to RNA editing. Resources reporting RNA editing sites from brain tissue have been published. Here, the authors provide an atlas of RNA editing events found in the aged and Alzheimer’s disease human brain tissue resulting in changes at protein level.